2008
DOI: 10.1161/circheartfailure.108.785485
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome, Inflammation, and Incident Heart Failure in the Elderly

Abstract: Background-Inflammation markers and metabolic syndrome (MetS) are associated with risk of congestive heart failure (CHF). We evaluated whether combining inflammation markers and MetS provided additive information for incident CHF and if incorporating inflammation markers to the MetS definition added prognostic information. Methods and Results-We studied 4017 men and women Ն65 years old, without baseline CHF or diabetes, participating in the Cardiovascular Health Study, an observational study with 12.2 years fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 50 publications
(39 reference statements)
3
41
0
4
Order By: Relevance
“…Today, it is considered that this inflammatory process of arterial wall is a consequence of different stimuli. Increased levels of adhesion molecules ICAM-1 and VCAM-1, and hsCRP in patients with IHD are reported by many authors [7]. Accordingly the similar results are obtained in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Today, it is considered that this inflammatory process of arterial wall is a consequence of different stimuli. Increased levels of adhesion molecules ICAM-1 and VCAM-1, and hsCRP in patients with IHD are reported by many authors [7]. Accordingly the similar results are obtained in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Probability value for trend over quartiles was Ͻ0.001 (log-rank test). Previous studies have reported associations between interleukin-6, tumor necrosis factor-␣, and C-reactive protein 8,10,13,26 and risk of HF. Ingelsson et al 9 reported relationships between erythrocyte sedimentation rate and incidence of HF.…”
Section: Discussionmentioning
confidence: 97%
“…184,185 Among individual components of MetS, high triglyceride level was the second most common (74%), after elevated blood pressure. 186 A high prevalence of triglyceride levels Ն150 mg/dL (72%) was also observed in patients with MetS and CVD.…”
Section: Prevalence Of Elevated Triglyceride In Metsmentioning
confidence: 99%